2018
DOI: 10.1176/appi.ajp.2017.17030316
|View full text |Cite
|
Sign up to set email alerts
|

Methylphenidate for Apathy in Community-Dwelling Older Veterans With Mild Alzheimer’s Disease: A Double-Blind, Randomized, Placebo-Controlled Trial

Abstract: Methylphenidate improved apathy in a group of community-dwelling veterans with mild Alzheimer's disease. Methylphenidate also improved cognition, functional status, caregiver burden, CGI scores, and depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 35 publications
2
79
2
Order By: Relevance
“…In trials investigating the use of methylphenidate in older patients with AD (mean age > 75), side effects were modest. However, symptomatic cardiovascular disease was an exclusion criterion in these trials [8,9]. Follow-up studies with cardiovascular monitoring are necessary to investigate whether repeated/prolonged methylphenidate administration is safe in older patients with cardiovascular disease before implemented in a clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In trials investigating the use of methylphenidate in older patients with AD (mean age > 75), side effects were modest. However, symptomatic cardiovascular disease was an exclusion criterion in these trials [8,9]. Follow-up studies with cardiovascular monitoring are necessary to investigate whether repeated/prolonged methylphenidate administration is safe in older patients with cardiovascular disease before implemented in a clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Methylphenidate may improve executive functioning by increasing norepinephrine and dopamine concentrations in the synaptic cleft [6]. While some studies in patients with dementia due to Alzheimer's disease (AD) have suggested an effect of methylphenidate on global cognition and on attention [7][8][9][10], other studies have not consistently supported the results [11]. In patients with VCI, only 1 small older open label longitudinal study in 15 patients with dementia found that methylphenidate slightly improved scores on the Mini-Mental State Examination (MMSE) [12].…”
Section: Introductionmentioning
confidence: 99%
“…apathy. A recent double-blind, randomized, placebo-controlled trial (DBRPCT) of methylphenidate (n = 60), a psychostimulant, showed that this drug improved the apathy evaluation scale-clinician version (AES-C) [8] score in patients with AD as compared with a placebo [9]. However, another DBRPCT of methylphenidate (n = 60), which used the apathy evaluation scale-informant (AES-I) [10], did not show this effect in patients with AD [11].…”
Section: Efficacy and Safety Of Psychostimulants For Alzheimer's Disementioning
confidence: 99%
“…The outcomes of our study were apathy (primary) scale score (i. e., frontal systems behavior scale apathy [14] from 1 study [15], AES-I from 2 studies [11,16], and AES-C from 1 study [9]), mini-mental state examination (MMSE) score [17], instrumental activities of daily living scale (IADL) score [18], Zarit burden interview [19] score, all-cause discontinuation rate, discontinuation due to adverse events, and incidence of individual adverse event. For evaluating apathy, 1 study [15] used frontal systems behavior scale apathy, 2 studies [11,16] used both AES-I and neuropsychiatric inventory (NPI) apathy score [20], and another study [9] used AES-C. There were 2 studies using the NPI apathy score.…”
Section: Data Sources Studies Sections and Data Extractionmentioning
confidence: 99%
See 1 more Smart Citation